Failure Mechanism of Anchored Rock under Constant Resistance Values of Cable Based on Particle Flow Code - Xiaoming Sun; Li Cui; Yong Zhang; Zuoxun Jiang; Lei Wang (Geofluids)
Focusing on a constant resistance (CR) cable, using particle flow code (PFC) software, the constant resistance characteristics of the cable are replaced by the servo control of the pallet, and the compressive mechanical properties of rock anchored on the free surface of a tunnel under different constant resistance values (CRVs) are studied. The results show that (1) during the compression failure process of the anchored rock, the stress-strain curve has a “double peak” feature, and the number of cracks has a “step” feature. The mutation point of the number of cracks corresponds to the two peak points of the stress-strain curve. (2) When the constant resistance value of the pallet is approximately 70%-80% of the absolute rigid support strength, the anchored rock has the maximum compressive strength, most stable deformation, maximum pallet energy absorption effect, and minimum number ratio of tensile-shear cracks. The mechanical properties of the CR-anchored rock are the best. (3) According to the different failure forms, the failure types of anchored rock under different CRVs are divided into the overall single-arch collapse type, connected double-arch collapse type, nonconnected double-arch collapse type, and local single-arch collapse type. The research results provide a reference for the design of a CRV and collapse prediction of the anchored surrounding rock.